A Meta-Analysis of the Relationship Between Emotional Intelligence and Academic Performance in Secondary Education: A Multi-Stream Comparison - Sánchez-Álvarez, Nicolás; Berrios Martos, María Pilar; Extremera, Natalio (Frontiers in Psychology, 2020)
This study was a quantitative meta-analysis of empirical research on the relationship between emotional intelligence (EI) and academic performance (AP) that included the three main theoretical models of EI. We conducted a computerized literature search in the main electronic databases. Forty-four of an initial 3,210 articles met the inclusion criteria. With 49 effect sizes and a cumulative sample size of 19,714 participants, we found significant heterogeneity indices indicating a variety of results. In general, the results of this study indicated a significant effect of EI on AP (¯Z = 0.26). This relationship was found to be higher in studies using ability EI instruments (¯Z = 0.31), than within studies using self-report EI instruments (¯Z = 0.24) and self-report mixed EI instruments (¯Z = 0.26). In the educational field, this meta-analysis provides information on the specific role of EI as a function of used measures. Some practical implications are discussed.